2021
DOI: 10.3390/toxics9100268
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Amendment Reduces the Availability of Pb in the Soil and Its Uptake in Lettuce

Abstract: The aim of this study was to investigate the ability of biochar amendment to reduce the availability of Pb in the soil and its uptake in lettuce (Lactuca sativa L. var. adela). Seedlings of lettuce were cultivated in Pb-contaminated soils, both with and without 5% biochar (w/w), as well as in a simplified soilless system (hydroponics) at the ecologically relevant Pb concentration of 100 µM, both with and without 1% biochar. Soils amended with biochar resulted in a ca. 50% reduction of the extractable (bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In present study, compared with the control, decreased metal uptake of Co, Cu, Fe, Mn, Zn, Cr and Ni in the BC 2% treatment was consistent with Fellet et al (2011). The biochar application increased the organic carbon content and pH in the tailings (Table 1), likely increasing metal complexation with organic matter and decreasing a relative proportion of the metallic cations at higher pH, with both of these processes limiting the mobility and availability of Cu ( (Vannini et al 2021). By contrast, shoot metal accumulation increased with increasing rate of wheat straw amendment (Table 3).…”
Section: Metal Accumulation In Perennial Ryegrass Shoots As In Uenced...supporting
confidence: 82%
“…In present study, compared with the control, decreased metal uptake of Co, Cu, Fe, Mn, Zn, Cr and Ni in the BC 2% treatment was consistent with Fellet et al (2011). The biochar application increased the organic carbon content and pH in the tailings (Table 1), likely increasing metal complexation with organic matter and decreasing a relative proportion of the metallic cations at higher pH, with both of these processes limiting the mobility and availability of Cu ( (Vannini et al 2021). By contrast, shoot metal accumulation increased with increasing rate of wheat straw amendment (Table 3).…”
Section: Metal Accumulation In Perennial Ryegrass Shoots As In Uenced...supporting
confidence: 82%
“…In line with this assumption, readily amended soils in the present study showed increases in both CEC and pH of 32% and 12%, respectively ( Table S1 ). Moreover, the shift in soil pH from weakly acidic to basic may also have limited the mobility and thus the availability of toxic elements for plants [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formerly, amending the Pb-polluted soil with BH and MKC reduced Pb uptake in spinach shoots [6]. Similarly, Vannini et al [62] confirmed that the addition of BH (5% w/w) in Pb-contaminated soil effectively reduced soil bioavailable fraction of Pb (up to 50%) and its accumulation in lettuce shoots (up to 50%). The lower availability of Pb in the soil and its uptake by spinach is because of multiple mechanisms associated with BH and MKC in the CIA, which are as follows: (i) the hydration process of MKC within the soil contributed to the conversion of Pb into extremely insoluble Pb-based compounds and struvite-K encapsulation [63] and (ii) the presence of extensive functional groups (like hydroxyl, carboxyl, and phenolic) on BH surfaces efficiently adsorbed Pb 2+ through precipitation, electrostatic interaction, and surface complexation [13].…”
Section: Lead Concentrations In Plant Parts and Plant-accessible Pbmentioning
confidence: 83%